Social Capital on The Performance of Microfinance Institutions of Agribusiness (MFI) in Indonesia - Analia, Devi; Budiman, Cipta; Hariance, Rika; Raesi, Syahyana (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
Social capital is an essential aspect in improving the performance of Agribusiness Microfinance Institutions (MFI). The Social capital discussed in this study is trust, norms, and networks. Meanwhile, the performance of MFI could be seen from aspects of MFI services, MFI management, credit supervision, and alleviation of bad loans. This study aims to determine the impact of social capital seen from the aspects of trust, networks, and norms in improving MFI performance in Padang City, West Sumatra. This study used the analysis method of Structural Equation Modeling (SEM) Second Order Condition. It collected primary data from trust, networks, and norms to improve MFI performance. The research was obtained from 60 MFI Customers. The study showed that social capital positively influences the performance of MFI in the city of Padang. Social capital, consisting of trust, norms, and networks, significantly affects MFI performance, such as MFI services, MFI management, credit supervision, and alleviating bad loans.